B cells in the pathogenesis and treatment of rheumatoid arthritis - Marston, Bethany (2010)
PURPOSE OF REVIEW: Our understanding of the multiple physiological and pathogenic functions of B cells in rheumatoid arthritis continues to expand. In turn, the availability of effective agents targeting the B cell compartment increases. In this review, we discuss novel insights into the roles of B cells in RA and recent evidence regarding the efficacy of B cell depletion and biomarkers of treatment response. RECENT FINDINGS: Recent data has further elucidated the requirements for the generation of ectopic lymphoid structures in the rheumatoid synovium, their frequency, and role in pathogenesis. Additional studies have described the phenotype of infiltrating B cells in the synovium and the unexpected role for B cells in bone homeostasis. In addition to pathogenic roles for B cells, there is also mounting evidence for regulatory B cell subsets that may play a protective role. New data on radiographic progression, efficacy in early disease, the role of re-treatment, and biomarkers of treatment response continue to refine the role of B cell depletion in the treatment armamentarium. SUMMARY: The past few years have seen new advances in immunology applied to the study of RA with surprising observations and interesting new insights into etiology and pathogenesis.